Eco-friendly management of fruit fly in mango - Kumar Singh, Sanjay; R, Megha; Kalia, Vinay; Yadav, Babita (Indian Horticulture, 2022)
Fruit fly infestation is the major concern in mango production in tropical and sub-tropical regions of the country. The adult flies infest by puncturing the surface of the mature fruits and lay the eggs that hatch into maggots. These maggots feed on flash of fruits thus make them unmarketable and unfit for human consumption. Depending upon the intensity of infestation, damage to fruits could be as high as 90%. Further, there is difference in intensity of infestation among the cultivars. Chemical control of fruit fly has been proposed but it do have health risks. Hence, the integrated pest management strategies of fruit flies in mango should be promoted whichinvolves orchard sanitation, use of methyl-eugenol traps, application of neem based oil sprays, protein bait spray, a male annihilation technique (MAT) with methyl-eugenol traps to kill males, need-based insecticidal cover sprays and integrated practices during fruit maturity